KLICK Syndrome Linked to a POMP Mutation Has Features Suggestive of an Autoinflammatory Keratinization Disease - Takeichi, Takuya; Akiyama, Masashi (Frontiers in Immunology, 2020)
Keratosis linearis with ichthyosis congenita and sclerosing keratoderma (KLICK) syndrome is a rare autosomal recessive skin disorder characterized by palmoplantar keratoderma, linear hyperkeratotic plaques, ichthyosiform scaling, circular constrictions around the fingers and numerous papules distributed linearly in the arm folds and on the wrists. Histologically, the affected skin shows hypertrophy and hyperplasia of the spinous, granular, and horny epidermal layers with mild infiltration of inflammatory cells in the upper dermis. There are fourteen patients with KLICK syndrome described in the literature and they all carry the same nucleotide deletion. Proteasome maturation protein (POMP), encoded by POMP, is a ubiquitously expressed protein that functions as a chaperone for proteasome maturation. KLICK syndrome is caused by a reduction in POMP levels that leads to proteasome insufficiency in differentiating keratinocytes. It is noteworthy that POMP is also known to be the causative gene for proteasome-associated autoinflammatory syndrome-2 (PRAAS2). It is considered that the disrupted proteasome assembly caused by the POMP mutation might lead to both skin inflammation and then hyperkeratosis in KLICK syndrome. Inflammation caused by the hyperactivation of innate immunity occasionally leads to inflammatory diseases of the skin, recently denoted as autoinflammatory keratinization diseases (AiKDs). We propose that KLICK syndrome caused by the specific 1bp nucleotide deletion mutation in the regulatory region of POMP might be in a spectrum of proteasome-associated phenotypes.